Identification of Jasmonate‐Mediated Physiological and Molecular Characteristics Correlated with the Brown Spot Resistance of Tobacco. Issue 5 (15th August 2019) - Zhang, Dingyu; Geng, Lina; Wang, Wenjing; Zhang, Jie; Zhang, Yan; Liu, Yanhua; Liu, Xinmin; Du, Yongmei; Zhang, Zhongfeng; Zhang, Hongbo
Abstract : Brown spot of tobacco ( Nicotiana tabacum L.), a fungal disease caused by Alternaria alternata, is widely spread across the world. In the present study, the physiological and transcriptional characteristics correlated with brown spot resistance were investigated using the resistant cultivar Beinhart 1000‐1 and a susceptible cultivar K326. The physiological assays revealed that Beinhart 1000‐1 was more sensitive to jasmonate (JA) than K326 in seed germination and root elongation assays. MYC2, a key regulator of the JA‐signaling pathway, exhibited a much higher expression level in Beinhart 1000‐1 than in K326 after pathogen challenge with A. Alternata or phytohormone treatment with JA, supporting the higher JA sensitivity of Beinhart 1000‐1. The transcriptional analyses showed that brown spot infection could provoke the expression of a set pathogenesis‐related ( PR ) genes and transcription factor genes from ethylene response factor (ERF), WRKY, and bHLH families, which are potentially involved in pathogen response. Furthermore, a number of these genes were induced to higher transcription levels by JA in Beinhart 1000‐1 than in K326. Cumulatively, this study revealed a set of JA‐mediated physiological and molecular factors that determine the brown spot resistance of tobacco and may provide cues for resistance breeding.